Fear of Pain and Fear of Falling among Younger and Older Adults with Musculoskeletal Pain Conditions - Ronald R Martin; Thomas Hadjistavropoulos; Donald R McCreary (Pain Research and Management)
BACKGROUND: The fear-avoidance model of pain accounts for the debilitating consequences of strong fear as a component of reactions to painful conditions (eg, movements become anxiety-provoking because they cause pain). The model, which is supported in the literature, posits that fear of pain interferes with recovery because it leads to avoidance of beneficial activity. Despite the high prevalence of pain among the elderly, investigations of fear of pain in this population are scarce. A related construct, fear of falling, has been studied among elderly (but not younger) adults as an age-specific concern.